(untitled) (Research, Society and Development, 2022)
Physiotherapy has been acting in various contexts and objectives of rehabilitation of patients with lumbar disc herniation and their quality of life, acting on the causes, symptoms, functional status, adherence to care and influencing the health costs, using assessment tools and resources for rehabilitation and health promotion as the Pilates method. This review aimed to discuss the Pilates method as a physiotherapeutic alternative to improve the quality of life of patients affected by lumbar disc herniation. The searches were carried out in the VHL, Scielo, PubMed, PEDro and Google Academic databases using combinations of the descriptors. We included publications that addressed the research objective, published from 2017 to 2022, with the full text available for free, in Portuguese, English and/or Spanish and that included at least one of the descriptors, and excluded duplicate articles, in other languages which were not selected, books, opinion articles, editorials, publications from scientific events and governmental publications. With the combinations of the descriptors and after applying the eligibility criteria, 6 articles resulted in this review. It was found that physiotherapy plays a significant role in the rehabilitation program with Pilates for patients with DHL. It presents a broad and essential approach that results in improved quality of life of the same, either by conducts, evaluative tools and/or the role played in the education of these patients. The physiotherapeutic approach in this scenario and population must continue to advance and further research is necessary.